Strengthening Modern Management-Based Community Organization Governance: Penelitian - Tomi Apra Santosa; Tri Suparyanto; Suhardy; Muchammad Chusnan Aprianto; Andri Kurniawan (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The challenges of social dynamics and technological developments require community organizations to have adaptive, transparent, and professional governance. This community service research aims to strengthen the governance of community organizations through the application of modern management principles, especially in the aspects of strategic planning, participatory leadership, and effective administrative systems. The method used in this activity is a participatory action research (PAR) approach that actively involves administrators and members of the organization in the process of training, mentoring, and continuous evaluation. This activity is carried out in three stages, namely assessment of organizational needs, modern management training, and implementation and monitoring. The results of the activity showed an increase in the capacity of the management in preparing strategic work plans, improving the organization's administrative system, and increasing member participation in decision-making. In addition, there is an increase in the effectiveness of internal and external communication of the organization which has an impact on strengthening institutional independence. In conclusion, strengthening community organizational governance based on modern management is able to increase the adaptability, effectiveness, and sustainability of the organization in dealing with changes in the social and economic environment.